Value of arteriography carotid in our environment - Esperón, Alejandro; López Chapuis, Daniel; Gómez Fossati, Carlos (Cirugía del Uruguay, 1996)
Arteriography is up to now the standard pre-operative method of study in extracraneal carotid pathology. lnformation a bout degree of stenosis and presence of ulceration or not in the atheromatous plaque is very important for the indication of carotid endarteroctomy.